Sensitivity Comparison of the Skin Prick Test and Serum and Fecal Radio Allergosorbent Test (RAST) in Diagnosis of Food Allergy in Children - Hamid Reza Kianifar; Alireza Pourreza; Farahzad Jabbari Azad; Hadis Yousefzadeh; Fatemeh Masomi (Reports of Biochemistry and Molecular Biology, 2016)
Background: Diagnosis of food allergy is difficult in children. Food allergies are diagnosed using several methods that include medical histories, clinical examinations, skin prick and serum-specific immunoglobulin E (IgE) tests, radio-allergosorbent test (RAST), food challenge, and supervised elimination diets. In this study we evaluated allergies to cow's milk, egg, peanut, and fish in children with suspected food allergies with skin prick tests and serum and feces RAST. Methods: Forty-one children with clinical symptoms of food allergies were enrolled in the study. Skin prick tests and serum and fecal RAST were performed and compared with challenge tests. Results: The most common sites of food allergy symptoms were gastrointestinal (82.9%) and skin (48.8%). 100% of the patients responded to the challenge tests with cow’s milk, egg, peanut, and fish. 65% of the patients tested positive with the skin prick test, 12.1% tested positive with serum RAST, and 29.2% tested positive with fecal RAST. Conclusions: The skin prick test was more sensitive than serum or fecal RAST, and fecal RAST was more than twice as sensitive as serum RAST.